Persistent Immune Activation in CVID and the Role of IVIg in Its Suppression - Paquin-Proulx, Dominic; Sandberg, Johan K. (Frontiers in Immunology, 2014)
Common variable immunodeficiency (CVID) is one of the most common and clinically important primary immune deficiencies. CVID patients have poor humoral immunity resulting in recurrent infections of the gastrointestinal and upper respiratory tracts, as well as increased incidence of some forms of cancers and autoimmune diseases. The treatment for CVID is IgG replacement, often given as intravenous immunoglobulins (IVIg). IVIg consists of monomeric IgG purified from pooled plasma from healthy donors and is used to treat an increasing number of conditions including autoimmune diseases. In the case of CVID, IVIg has mainly been seen as reconstitution therapy, providing patients with pathogen-specific antibodies. Recent evidence shows that IVIg has diverse effects on the immune system of CVID patients, and one important component is that IVIg alleviates the state of chronic immune activation. In this review we will discuss causes and consequences of persistent immune activation in CVID, possible underlying mechanisms for how IVIg treatment reduces immune activation, and implications for our understanding of primary as well as acquired immune deficiencies.